Development of Collagen-Based 3D Matrix for Gastrointestinal Tract-Derived Organoid Culture - Joo Hyun Jee; Dong Hyeon Lee; Jisu Ko; Soojung Hahn; Sang Yun Jeong; Han Kyung Kim; Enoch Park; Seon Young Choi; Sukin Jeong; Joong Woon Lee; Han-Jun Cho; Min-Soo Kwon; et al. (Stem Cells International)
Organoid is a cell organization grown in a three-dimensional (3D) culture system which represents all characteristics of its origin. However, this organ-like structure requires supporting matrix to maintain its characteristics and functions. Matrigel, derived from mouse sarcoma, has often been used as the supporting matrix for organoids, but the result may not be desirable for clinical applications because of the unidentified components from the mouse sarcoma. On the other hand, natural characteristics of collagen emphasize toxic-free friendly niche to both organoid and normal tissue. Hence, this study attempts to develop a new, collagen-based matrix that may substitute Matrigel in organoid culture. Collagen-based matrix was made, using type 1 collagen, Ham’s F12 nutrient mixture, and bicarbonate. Then, characteristics of mouse colon organoids were analyzed by morphology and quantitative messenger RNA (mRNA) expression, revealing that the mouse colon organoids grown in the collagen-based matrix and in Matrigel had quite similar morphology, specific markers, and proliferative rates. Mouse small intestine–derived organoids, stomach-derived organoids, and human colon–derived organoids were also cultured, all of which were successfully grown in the collagen-based matrix and had similar properties compared to those cultured in Matrigel. Furthermore, possibility of organoid transplantation was observed. When mouse colon organoids were transplanted with collagen matrix into the EDTA-colitis mouse model, colon organoids were successfully engrafted in damaged tissue. For that reason, the use of collagen-based matrix in organoid culture will render organoid cultivation less expensive and clinically applicable.